DISCIPLINE «TECHNOLOGY OF HOTEL AND CATERING TRADE» IN THE SYSTEM OF PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN THE HOSPITALITY INDUSTRY - Kulinka, Yuliia; Serohina, Iryna; Hrushnik, Olha; Pisna, Tetiana; Petrova, Alona (Revista Inclusiones, 2020)
The experience of international tourism has been analyzed in the article, it allows us to say: the domestic tourism is inferior to the world standards, because there is an unsatisfactory quality of educational services, little use of innovative forms of organization of the sphere of hotel - catering trade and tourism, there are a lot of acute questions to the quality and culture of public service. That is why there is a need to make changes in the content of educational training programs and to introduce new directions, forms and methods of work. Technical and industrial tourism is rapidly developing in the city of Kryvyi Rih (Ukraine), so the market of services should be provided by the qualified specialists of the hospitality industry. Kryvyi Rih State Pedagogical University provides training for the specialists in the specialties 015 “Professional education (service sector)” and 242 “Tourism”. The leading discipline of professional training is the study of the technology of hotel and restaurant business, based on the principles of a competence-based approach and the development of professional skills of students based on such forms of work as: master classes, trainings, case methods, excursions, and so on.